2015
DOI: 10.1080/01635581.2015.1085581
|View full text |Cite
|
Sign up to set email alerts
|

Berberine and Curcumin Target Survivin and STAT3 in Gastric Cancer Cells and Synergize Actions of Standard Chemotherapeutic 5-Fluorouracil

Abstract: Aberrantly expressed survivin and STAT3 signaling have emerged as major determinants of chemoresistance in gastric cancer. We evaluated effects of potent herbal derivatives curcumin, berberine, and quercetin on STAT3 signaling, survivin expression, and response to 5-fluorouracil (5-FU) treatment in gastric cancer cells (AGS). Cytotoxic and inhibitory effects of berberine, curcumin, and quercetin alone or in combination with 5-FU were examined by MTT assay, and their effect on survivin, STAT3, and the phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 42 publications
3
57
0
Order By: Relevance
“…Flow-cytometric analysis of apoptotic cell death was performed as indicated earlier [44]. Briefly, cells were harvested, washed with PBS, and incubated with fluorescein isothiocynate (FITC) conjugated Annexin V and propidium iodide (PI) according to the instruction of Annexin V apoptosis detection kit.…”
Section: Methodsmentioning
confidence: 99%
“…Flow-cytometric analysis of apoptotic cell death was performed as indicated earlier [44]. Briefly, cells were harvested, washed with PBS, and incubated with fluorescein isothiocynate (FITC) conjugated Annexin V and propidium iodide (PI) according to the instruction of Annexin V apoptosis detection kit.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found to have antitumor, anti-inflammatory, and apoptotic properties both in vitro and in vivo 14–16. Studies have demonstrated that curcumin has the potential to be combined with chemotherapeutics for GC 17,18. These reports focused mainly on the role of curcumin in resistant GC cells through the activation of survivin and STAT3 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these data indicate that Curcumin reduces the expression of MTA1 gene through upregulation of miR-30c-5p in Paclitaxel-resistant NSCLC cells. Since Curcumin has been reported to regulate signaling molecules and transcriptional factors, [15][16][17] further studies can be done to explore which signaling molecule and/or transcriptional factor is required for Curcumin-increased miR-30c-5p expression in Paclitaxel-resistant NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] As an anticancer agent, Curcumin has been demonstrated to regulate transcriptional factors, signaling molecules, and microRNAs (miRNAs), such as signal transducer and activator of transcription 3 (STAT3), activation protein 1 (AP-1), Forkhead box O1 (FOXO1), nuclear factor kappa B (NF-κB), Akt, reactive oxygen species (ROS), miR-208, and miR-21. [14][15][16][17][18] Our current study revealed that Curcumin could increase the sensitivity of Paclitaxel-resistant NSCLC cells to Paclitaxel in vitro. Further studies need to be done to explore the potential mechanism by which Curcumin enhances the sensitivity of Paclitaxel-resistant NSCLC cells to Paclitaxel.…”
Section: Introductionmentioning
confidence: 99%